Replacing Inpatient Care by Outpatient Care in the Treatment of Deep Venous Thrombosis – An Economic Evaluation - van den Belt, Angelique G. M.; Bossuyt, Patrick M. M.; Prins, Martin H.; Gallus, Alexander S.; Büller, Harry R.; for the TASMAN Study Group (Thrombosis and Haemostasis, 1998)
Two clinical trials in patients with acute deep venous thrombosis have indicated that the outpatient management with fixed-dose, subcutaneous low-molecular-weight heparin is at least as effective and safe as inpatient treatment with unfractionated intravenous heparin with respect to recurrent venous thromboembolism and major bleeding. We performed an economic evaluation alongside one of these trials to assess the cost consequences of the outpatient management strategy. Data were collected through case record forms, complemented by a prospective questionnaire in 78 consecutive patients, interviews with health care providers, and hospital data bases. Our study demonstrated that seventy-five percent of patients allocated to low-molecular-weight heparin received treatment either entirely at home or after a brief hospital stay. Fifteen percent of these patients required professional domiciliary care. Within-centre comparisons of resource utilisation in terms of natural units showed that outpatient management with low-molecular-weight heparin reduced the average number of hospital days in the initial treatment period in nine centres by 59 percent (95% CI: 43 to 71 percent) accompanied by a limited increase in outpatient and professional domiciliary care. The average reduction in hospital days at the end of follow up was 40 percent (95% CI: 25 to 54 percent). A cost-minimisation analysis, focusing on resource utilisation directly related to the treatment of deep venous thrombosis and associated costs in one centre demonstrated a cost reduction of 64 percent (95% CI: 56 to 72 percent) with the outpatient management with low-molecular-weight heparin. These data suggest that outpatient management of patients with proximal venous thrombosis using low-molecular-weight heparin reduces resource utilisation and total treatment cost. Implementation should be preceded by a cautious evaluation of a potential cost shifting and organisational prerequisites.